Emaranhamento eletrônico em moléculas de pontos quânticos semicondutores - Oliveira, Patrícia Aparecida Almeida de (2015)
In this work, we study the dynamics of entanglement between two eletronic qubits inside two coupled quantum molecules, where each molecule is consisting of two semiconductor quantum dots. Our first interest is to explore the production of maximally entangled states in the two level system not considering dissipation. Using the Bell states, we define a new basis for the system of interest, which allows to obtain a new Hamiltonian for the quantum molecules. To analyze the characteristics of eigenstates of the Hamiltonian which describes the quantum molecules, we use a measure of entanglement called concurrence. From the new base, we verify the behavior the dynamics of entanglement by manipulating the physical parameters of the system as the detuning and the tunneling between the quantum dots contained in molecules and the Coulomb interaction.We identified a set of physical parameters which are linked to the creation of maximally entangled states and other conditions where it is not possible to entangle the subsystems.